IMPLEMENTASI MODEL PEMBELAJARAN JURISPRUDENSIAL DALAM MENUMBUHKAN KEPEKAAN SOSIAL SISWA PADA MATERI TOLERANSI AGAMA KELAS XI RPL-B SMK NEGERI 3 TUBAN - Muhammad Faliq Mubarrok Ilmi; Iis Aisaroh; Anis Sa’adah; Muslimin (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to describe the process of implementing the jurisprudential learning model in religious tolerance materials, identify the obstacles faced, and analyze the increase in social sensitivity of grade XI RPL-B students at SMK Negeri 3 Tuban. The research method used is a qualitative approach with a descriptive case study design. Data were collected through direct observation and in-depth interviews of 36 students selected through purposive sampling techniques. Data analysis was carried out using the Miles and Huberman interactive model which included data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of the jurisprudential model is carried out through the presentation of contextual issues, group discussions, and the use of reflective questioning techniques (Socratic test). Despite constraints such as limited time and students' cognitive readiness, this model has been shown to be effective in increasing students' social sensitivity. This is shown by the ability of students to build empathetic arguments, respect differences in beliefs, and be able to take a wise stance in responding to the issue of religious pluralism in the school environment.